1998
DOI: 10.1016/s1010-7940(97)00308-4
|View full text |Cite
|
Sign up to set email alerts
|

Transmyocardial laser revascularisation in acutely ischaemic myocardium1

Abstract: Objective: Although recent experience suggests that transmyocardial laser revascularisation (TMLR) relieves angina, its mechanism of action remains undefined. We examined its functional effects and analysed its morphological features in an animal model of acute ischaemia. Methods: A total of 15 pigs were randomised to ligation of left marginal arteries (infarction group, n =5), to TMLR of the left lateral wall using a holmium:yttrium-aluminium garnet (Ho:YAG) laser (laser group, n= 5), and to both (laser-infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although the exact mechanism of TMLR is unknown, improved perfusion and relief of symptoms after treatment could result from patent (open) tunnels created by the laser or from laser-induced angiogenesis. While some studies have found evidence of tunnel patency and of angiogenesis (Frazier, March & Horvath 1999 and references therein; Kadipasaoglu et al 1997;Berwing et al 1997) others have failed to find such evidence (Hardy et al 1987;Landreneau et al 1991;Mueller et al 1998). Schofield et al (1999) found no evidence of improved cardiac function or myocardial perfusion, although they did find that the treatment provided relief from angina symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism of TMLR is unknown, improved perfusion and relief of symptoms after treatment could result from patent (open) tunnels created by the laser or from laser-induced angiogenesis. While some studies have found evidence of tunnel patency and of angiogenesis (Frazier, March & Horvath 1999 and references therein; Kadipasaoglu et al 1997;Berwing et al 1997) others have failed to find such evidence (Hardy et al 1987;Landreneau et al 1991;Mueller et al 1998). Schofield et al (1999) found no evidence of improved cardiac function or myocardial perfusion, although they did find that the treatment provided relief from angina symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Whittaker et al [30,31] and others [32] found that TMLR does not increase myocardial blood flow in a region after ligature of a coronary artery, except if the channels were created 2 months before the coronary occlusion. A favorable effect of TMLR during acute myocardial infarction could also not be proven [33,34].…”
Section: Experimental Studies and Potential Mechanisms Of The Laser Ementioning
confidence: 95%
“…As with TMLR,14 the mechanisms of action during PMLR are unclear. Proposed laser mechanisms with insufficient and/or contradictory evidence include direct perfusion,1518 microvascular angiogenesis,1923 and cardiac afferent denervation 2427. There is also insufficient evidence to support placebo effect13,28 and change in attitudes and expectations24 towards angina as significant factors in symptom relief.…”
Section: Introductionmentioning
confidence: 99%